Positive personality-trait-like individual differences in athletes from individual- and team sports and in non-athletes. (September 2016) - Laborde, Sylvain; Guillén, Félix; Mosley, Emma
Abstract: The aim of this study was twofold: first, to replicate the positive association between sport participation and positive personality-trait-like individual differences (PTLID), and second to investigate whether athletes from individual and team sports would differ regarding positive PTLID. Participants of this study – 600 non-athletes and 600 athletes (280 practicing individual sports, 320 team sports) – completed a battery of questionnaires designed to assess five characteristics grouped under the umbrella term of positive PTLID, including: perseverance, positivity, resilience, self-esteem, and self-efficacy. A first MANOVA revealed that athletes scored systematically higher than non-athletes on positive PTLID. A second MANOVA showed that athletes from individual sports scored higher on positive PTLID than athletes from team sports. This could be explained by the individual responsibility that comes from performing alone and the need to possess greater enduring personal dispositions to succeed. Highlights: Personality-trait-like individual differences (PTLID). Positive PTLID: self-efficacy, positivity, resilience, self-esteem, and perseverance. Positive PTLID positively associated with sport participation. Individual sports athletes higher on positive PTLID than team sports athletes.